Calcium/calmodulin-dependent protein kinase OsDMI3 positively regulates saline-alkaline tolerance in rice roots. (1st November 2020) - Ni, Lan; Wang, Shuang; Shen, Tao; Wang, Qingwen; Chen, Chao; Xia, Jixing; Jiang, Mingyi
ABSTRACT: Soil saline-alkalization is a major environmental stress that impairs plant growth and crop productivity. Plant roots are the primary site for the perception of soil stresses; however, the regulation mechanism engaged in the saline-alkaline stress response in plant roots is not well understood. In this study, we identified how a rice Ca 2+ /calmodulin-dependent protein kinase, OsDMI3, confers saline-alkaline tolerance in rice root growth. We measured the OsDMI3 activity by an in-gel kinase assay, Na + content by NaHCO3 treatment, and Na + and H + fluxes by noninvasive micro-test technology (NMT). Furthermore, a real-time reverse-transcription polymerase chain reaction (RT-PCR) analysis was performed to identify the genes upregulated in response to NaHCO3 treatment in rice roots. The results showed that NaHCO3 significantly increased OsDMI3 expression and activity in rice roots. This was consistent with the results of Na + content and NMT that indicated OsDMI3 promoted root elongation under saline-alkaline stress by reducing root Na + and H + influx. Moreover, real-time RT-PCR analysis revealed that OsDMI3 up-regulated the transcript levels of OsSOS1 and PM-H + -ATPase genes OsA3 and OsA8 in saline-alkaline stressed rice plants. Collectively, our results suggest that OsDMI3 could promote saline-alkaline tolerance in rice roots by modulating the Na + and H + influx. These findings provide an important genetic target for protection of growth in rice exposed to saline-alkaline stress.